Japan Nosocomial Infections Surveillance (JANIS): Current Status, International Collaboration, and Future Directions for a Comprehensive Antimicrobial Resistance Surveillance System - Kajihara, Toshiki; Yahara, Koji; Hirabayashi, Aki; Shibayama, Keigo; Sugai, Motoyuki (Japanese Journal of Infectious Diseases, 2021)
Japan Nosocomial Infections Surveillance (JANIS) is one of the largest national antimicrobial resistance (AMR) surveillance systems in the world. The JANIS Clinical Laboratory division collects comprehensive specimen-based data from diagnostic microbiology laboratories of participating hospitals to monitor the isolation rate of 11 major bacteria and specific AMR bacteria, and creates antibiograms of approximately 20 bacterial species. Data on the JANIS web database system are also annually tabulated and shared with the WHO Global Antimicrobial Resistance Surveillance System. To create a network of international AMR surveillance systems among Asian countries, Japan is developing an international web database system named ASIan Antimicrobial Resistance Surveillance Network (ASIARS-Net) based on the JANIS system; ASIARS-Net is an open-source database and confidentially available at almost no cost. JANIS continues to evolve in multiple directions; some are discussed at the end of this review.